Interleukin-10 mediated immune regulation after stem cell transplantation: Mechanisms and implications for therapeutic intervention. (August 2019) - Zhang, Ping; Hill, Geoffrey R.
Highlights: The equilibrium between IL-10, immune cells, commensal microbes and host tissues is critical for immune tolerance. CD4 T cells, especially Tr1 cells, are predominant sources of IL-10 after allogenic SCT. Therapeutic interventions exploiting IL-10 have the potential to prevent and treat GVHD. Abstract: Interleukin-10 (IL-10) is a multi-faceted anti-inflammatory cytokine which plays an essential role in immune tolerance. Indeed, deficiency of IL-10 or its receptor results in aberrant immune responses that lead to immunopathology. Graft-versus-host disease (GVHD) is the limiting complication of allogeneic stem cell transplantation (SCT) and results from an imbalance in pathological versus regulatory immune networks. A number of immune cells exert their immunomodulatory role through secretion of IL-10 or induction of IL-10-secreting cells after SCT. Type-1 regulatory T cells (Tr1 cells) and FoxP3 + regulatory T cells (Tregs ) are predominant sources of IL-10 after SCT and the critical role of this cytokine in preventing GVHD is now established. Recently, intriguing interactions among IL-10, immune cells, commensal microbes and host tissues in the gastrointestinal (GI) tract and other barrier surfaces have been uncovered. We now understand that IL-10 secretion is dynamically modulated by the availability of antigen, co-stimulatory signals, cytokines, commensal microbes and their metabolites in the microenvironment. In this review, we provide an overview of the control of IL-10 secretion and signaling after SCT and the therapeutic interventions, with a focus on Tr1 cells.